Quality of vision with spectacles, special silicone hydrogel and gas permeable contact lenses in keratoconic patients - González-Méijome, José Manuel (2013)
Purpose: To evaluate optical quality and visual function in keratoconus patients corrected with RGP contact lenses and a novel special design of silicone hydrogel contact lens. Materials and methods: Twelve eyes of six patients with keratoconus were enrolled to experience a new soft contact lens (Soft-K) for keratoconus made of a silicone-hydrogel material and the outcomes were compared to the performance with gas permeable lenses and spectacles. The three situations were compared for monocular and binocular high (100%) and low contrast (10%) ETDRS LogMAR visual acuity and contrast sensitivity function (CSF). Results: On average, there was an improvement of more than two lines in visual acuity over spectacle correction and this is statistically significant for both gas permeable (GP) and Soft-K lens (p < 0.001). Visual acuity was not significantly different between GP and Soft-K lens for high contrast acuity but was slightly higher with GP lens for low contrast under binocular conditions. Monocular CSF showed a marked improvement with the Soft-K lens and GP, compared to spectacles correction, particularly for medium and high frequencies; conversely. Conclusion: Soft-K silicone hydrogel soft contact lens produces a clinical and statistically significant improvement in visual acuity and contrast sensitivity function over spectacle correction.